A specific CD4 epitope bound by tregalizumab mediates activation of regulatory T cells by a unique signaling pathway. Issue 4 (16th December 2014) - Helling, Bianca; König, Martin; Dälken, Benjamin; Engling, Andre; Krömer, Wolfgang; Heim, Katharina; Wallmeier, Holger; Haas, Jürgen; Wildemann, Brigitte; Fritz, Brigitte; Jonuleit, Helmut; Kubach, Jan; et al.
Abstract : CD4 + CD25 + regulatory T cells (Tregs) represent a specialized subpopulation of T cells, which are essential for maintaining peripheral tolerance and preventing autoimmunity. The immunomodulatory effects of Tregs depend on their activation status. Here we show that, in contrast to conventional anti‐CD4 monoclonal antibodies (mAbs), the humanized CD4‐specific monoclonal antibody tregalizumab (BT‐061) is able to selectively activate the suppressive properties of Tregs in vitro . BT‐061 activates Tregs by binding to CD4 and activation of signaling downstream pathways. The specific functionality of BT‐061 may be explained by the recognition of a unique, conformational epitope on domain 2 of the CD4 molecule that is not recognized by other anti‐CD4 mAbs. We found that, due to this special epitope binding, BT‐061 induces a unique phosphorylation of T‐cell receptor complex‐associated signaling molecules. This is sufficient to activate the function of Tregs without activating effector T cells. Furthermore, BT‐061 does not induce the release of pro‐inflammatory cytokines. These results demonstrate that BT‐061 stimulation via the CD4 receptor is able to induce T‐cell receptor‐independent activation of Tregs. Selective activation of Tregs via CD4 is a promising approach for the treatment of autoimmune diseases where insufficient Treg activity has been described. Clinical investigation of this new approach is currently ongoing.